Comparison and Functional Analysis of Chemosensory Protein Genes From Eucryptorrhynchus scrobiculatus Motschulsky and Eucryptorrhynchus brandti Harold - Wang, Qian; Wen, Xiaojian; Lu, Yi; Wen, Junbao (Frontiers in Physiology, 2021)
The tree-of-heaven root weevil (Eucryptorrhynchus scrobiculatus) and the tree-of-heaven trunk weevil (Eucryptorrhynchus brandti) are closely related species that monophagously feed on the same host plant, the Ailanthus altissima (Mill) Swingle, at different locations. However, the mechanisms of how they select different parts of the host tree are unclear. As chemosensory systems play important roles in host location and oviposition, we screened candidate chemosensory protein genes from the transcriptomes of the two weevils at different developmental stages. In this study, we identified 12 candidate chemosensory proteins (CSPs) of E. scrobiculatus and E. brandti, three EscrCSPs, and one EbraCSPs, respectively, were newly identified. The qRT-PCR results showed that EscrCSP7/8a/9 and EbraCSP7/8/9 were significantly expressed in adult antennae, while EscrCSP8a and EbraCSP8 shared low sequence identity, suggesting that they may respond to different odorant molecule binding. Additionally, EbraCSP6 and EscrCSP6 were mainly expressed in antennae and proboscises and likely participate in the process of chemoreception. The binding simulation of nine volatile compounds of the host plant to EscrCSP8a and EbraCSP8 indicated that (1R)-(+)-alpha-pinene, (–)-beta-caryophyllene, and beta-elemen have higher binding affinities with EscrCSP8a and lower affinities with EbraCSP8. In addition, there were seven, two, and one EbraCSPs mainly expressed in pupae, larvae, and eggs, respectively, indicating possible developmental-related roles in E. brandti. We screened out several olfactory-related possible CSP genes in E. brandti and E. scrobiculatus and simulated the binding model of CSPs with different compounds, providing a basis for explaining the niche differentiation of the two weevils.